Community-Driven Brand Loyalty: The Interplay of Experience, Benefits, and Engagement - Hermawan, Indra; Ginting, Paham; Rini, Endang Sulistya (Asian Journal of Management Analytics, 2024)
The aim of this study is to conduct a comprehensive analysis of the effects of community experience and perceived community benefits on brand loyalty, with brand engagement serving as an intervening variable. Employing a quantitative survey methodology with an associative approach, this research focuses on members of the Sampoerna Retail Community in Area Medan 2, comprising a population of 2,293 individuals. A sample of 180 respondents was selected. Data collection utilized a structured questionnaire, and analytical methods included descriptive analysis and PLS-SEM, ensuring a robust evaluation of the relationships among the key variables. The findings indicate that community experience and the perception of community benefits both exert a positive and statistically significant influence on brand loyalty. While community experience positively influences brand engagement, this relationship does not achieve statistical significance. In contrast, the perception of community benefits significantly affects brand engagement. Furthermore, brand engagement positively impacts member loyalty. Notably, while brand engagement does not mediate the relationship between perceived community benefits and brand loyalty, it does mediate the relationship between community experience and brand loyalty. This research enhances the understanding of the dynamics among these variables within the research context.